A educação financeira como tema transversal na educação básica - Teixeira, Simone de Souza (2020)
In this work, we present the results of the questionnaires, applied to teachers and students of schools of basic education, addressing previous financial knowledge of those involved and their relationship with the terms of Financial Education studied in schools. In Chapter 1, we dedicate ourselves to understanding what Financial Education is and how it has been implemented in Brazil. In Chapter 2, we present the results and analyzes of the questionnaires applied to students and teachers of basic education. In Chapter 3, we present some subjects that are generally in the headlines of newspapers and magazines and therefore deserve attention at school when approaching Financial Education as a transversal theme. We also discussed the concepts necessary for the student to have autonomy to read these subjects. We finish our work aware that people do not understand the financial cycle in which they are involved. They fail to understand most of the issues that make up the daily headlines of newspapers and magazines and this ends up interfering with their planning and quality of life, as well as their ability to exercise full citizenship. Thus, it is necessary to put into practice the effective work with Financial Education in schools, since the real implementation of this proposal is at an early stage in Brazil, that is, it has practically not yet left the paper.